Spontaneous regression of renal cell carcinoma - Janiszewska, Anna Daria; Poletajew, Sławomir; Wasiutyński, Aleksander (Contemporary Oncology/Współczesna Onkologia, 2013)
Renal cell carcinoma (RCC) comprises 3–4% of all malignant tumours among adults in Poland. Spontaneous regression of RCC is a rare but well-known phenomenon. Its frequency is estimated to be approximately 1% and a large part of the percentage is accounted for by the regression of pulmonary metastases in the course of clear type of RCC treatment. We searched PubMed, Embase and SciVerse Scopus databases, identifying 59 case reports of spontaneous regression of RCC. Those medical histories come from reports from around the world and date back up to 40 years. This review includes their analysis as well as description of possible explanations of this phenomenon postulated by different authors, including both misdiagnosis and immunological reactions. This study indicates that reliable diagnostics and reporting of all the cases of spontaneous regression play a key role, as this is the only method which enables a better perspective in understanding this issue.